HNF1A recruits KDM6A to activate differentiated acinar cell programs that suppress pancreatic cancer. (10th March 2020) - Kalisz, Mark; Bernardo, Edgar; Beucher, Anthony; Maestro, Miguel Angel; del Pozo, Natalia; Millán, Irene; Haeberle, Lena; Schlensog, Martin; Safi, Sami Alexander; Knoefel, Wolfram Trudo; Grau, Vanessa; de Vas, Matías; et al.
Abstract: Defects in transcriptional regulators of pancreatic exocrine differentiation have been implicated in pancreatic tumorigenesis, but the molecular mechanisms are poorly understood. The locus encoding the transcription factor HNF1A harbors susceptibility variants for pancreatic ductal adenocarcinoma (PDAC), while KDM6A, encoding Lysine‐specific demethylase 6A, carries somatic mutations in PDAC. Here, we show that pancreas‐specific Hnf1a null mutant transcriptomes phenocopy those of Kdm6a mutations, and both defects synergize with Kras G12D to cause PDAC with sarcomatoid features. We combine genetic, epigenomic, and biochemical studies to show that HNF1A recruits KDM6A to genomic binding sites in pancreatic acinar cells. This remodels the acinar enhancer landscape, activates differentiated acinar cell programs, and indirectly suppresses oncogenic and epithelial–mesenchymal transition genes. We also identify a subset of non‐classical PDAC samples that exhibit the HNF1A/KDM6A ‐deficient molecular phenotype. These findings provide direct genetic evidence that HNF1A deficiency promotes PDAC. They also connect the tumor‐suppressive role of KDM6A deficiency with a cell‐specific molecular mechanism that underlies PDAC subtype definition. Synopsis: Whether defective transcriptional control of cell differentiation contributes to the development of pancreatic ductal adenocarcinoma (PDAC) remains poorly understood. Here, cooperation of transcription factor HNF1A with lysine‐specific demethylase 6A (KDM6A/UTX) is found to activate an epithelial program in pancreatic acinar cells and to impair Kras G12D ‐driven tumorigenesis. HNF1A recruits KDM6A to target genes that specify acinar cell epithelial identity. HNF1A and KDM6A regulate a common transcriptional program that is defective in non‐classical human PDAC. Hnf1a loss in mice cooperates with Kras G12D mutation and recapitulates Kdm6a‐deficient PDAC. Abstract : Cooperation between a transcription factor and an epigenetic modifier reveals how defective transcriptional control can contribute to development of pancreatic ductal adenocarcinoma.